Using Public-Private Partnerships and Energy Savings Contracts to Fund DoD Mobile Assets - San Miguel, Joseph G.; Summers, Donald E. (2006)
The Department of Defense (DoD) has engaged in numerous Public-Private Partnership (PPP) ventures such as outsourcing of services and privatization of military housing. In the past, the activities considered for PPPs have been primarily administrative and support functions. This research explores the possibility of expanding the use of PPPs to enhance the DoD combat and combat-support functions. First, to better understand how PPPs function (the partnership relationships and financing arrangements), we examine Hannon Armstrong's "fee for service contract" solution to the lack of appropriated funds for establishing a vital fiber-optic link near the Arctic Circle. Next, we explore the history of Energy Savings Performance Contracts (ESPCs) and their potential application to re-engining the Air Force's B-52H through PPPs. Historically, this program has only been used for fixed assets, not mobile assets like engines. There is little debate over the success of ESPC contracts in reducing energy consumption, but their use in DoD mobile assets is new. Finally, we conclude that applying ESPCs to mobile assets has the potential to reduce energy consumption, save millions of dollars and increase combat efficiency. The original document contains color images.